2007
DOI: 10.3354/meps339083
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic interactions between the bacillariophyte Skeletonema costatum and the raphidophyte Heterosigma akashiwo

Abstract: We investigated growth interactions between Skeletonema costatum (Greville) Cleve and Heterosigma akashiwo (Hada) Hada ex Hara et Chihara using bi-algal cultures under axenic conditions. When inoculated at high cell densities, growth of both species was coincidentally suppressed. In other combinations of inoculation density, the species first reaching stationary phase substantially reduced maximum cell densities of the other species. When cultured together under conditions without cell contact, growth of S. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 25 publications
(34 reference statements)
7
57
1
1
Order By: Relevance
“…Thus, it is likely that the allelopathic effects of H. akashiwo were both species-specific and dependent upon the cell density of the target species. This supported the finding of a previous study (Yamasaki et al, 2007), and suggested that allelopathy drives the alternation of the two species in the field. Similarly, the diatom T. rotula was also strongly inhibited depending upon the concentration of protein dissolved in the filtrate of H. akashiwo (Figure 2, Supplementary Figure 2).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Thus, it is likely that the allelopathic effects of H. akashiwo were both species-specific and dependent upon the cell density of the target species. This supported the finding of a previous study (Yamasaki et al, 2007), and suggested that allelopathy drives the alternation of the two species in the field. Similarly, the diatom T. rotula was also strongly inhibited depending upon the concentration of protein dissolved in the filtrate of H. akashiwo (Figure 2, Supplementary Figure 2).…”
Section: Resultssupporting
confidence: 82%
“…Similarly, APPCs were detected by a dot-blot analysis of axenic cultures of H. akashiwo at densities 1 Â 10 5 cells per ml (Supplementary Figure 3b), at which H. akashiwo can inhibit S. costatum growth in the laboratory experiments (Yamasaki et al, 2007); these findings supported the conclusion drawn from the field study (Figures 6b and c) that APPCs can affect the growth of other phytoplankton in the field. A comparison of dot-blots from 40 mg ml -1 culture filtrate and from the dense bloom sampled on 8 June (Figure 6d) showed a similar stain density in both, indicating a similar amount of allelopathic activity, which was sufficient to suppress S. costatum growth.…”
Section: Significance Of Appcs In the Fieldsupporting
confidence: 78%
See 2 more Smart Citations
“…Strains of H. akashiwo, C. neogracile, Nannochloropsis sp., and the haptophyte Pavlova lutheri (Droop) Green, 1975 were inoculated at a density of 5,000 cells mL 1 into 200-mL glass flasks (n=3) containing 150 mL modified SWM-3 medium (Yamasaki et al 2007). After incubation for 12 d at 25°C under 150 ( 10) μmol photons m 2 s 1 of cool-white fluorescent illumination on a 12 : 12 h light : dark cycle, 100 mL from each of the three replicate flasks was centrifuged at 700 g for 15 min, and the cell pellet from each sample was frozen at -30°C until used for total sugar and acidic sugar determination.…”
mentioning
confidence: 99%